Porcine low-density lipoprotein receptor plays an important role in classical swine fever virus infection - Elena Leveringhaus; Robin Poljakovic; Gina Herrmann; Gleyder Roman-Sosa; Paul Becher; Alexander Postel (Emerging Microbes and Infections)
Several cellular factors have been reported to be required for replication of classical swine fever virus (CSFV), a member of the genus Pestivirus within the family Flaviviridae. However, many steps of its replication cycle are still poorly understood. The low-density lipoprotein receptor (LDLR) is involved in cell entry and post-entry processes of different viruses including other members of the Flaviviridae. In this study, the relevance of LDLR in replication of CSFV and another porcine pestivirus, Bungowannah pestivirus (BuPV), was investigated by antibody-mediated blocking of LDLR and genetically engineered porcine cell lines providing altered LDLR expression levels. An LDLR-specific antibody largely blocked infection with CSFV, but had only a minor impact on BuPV. Infections of the genetically modified cells confirmed an LDLR-dependent replication of CSFV. Compared to wild type cells, lower and higher expression of LDLR resulted in a 3.5-fold decrease or increase in viral titers already 20 h post infection. Viral titers were 25-fold increased in LDLR-overexpressing cells compared to cells with reduced LDLR expression at 72 h post infection. The varying LDLR expression levels had no clear effect on permissivity to BuPV. A decoy receptor assay using recombinant soluble LDLR provided no evidence that LDLR may function as a receptor for CSFV or BuPV. Differences in their dependency on LDLR suggest that CSFV and BuPV likely use different mechanisms to interact with their host cells. Moreover, this study reveals similarities in the replication cycles of CSFV and other members of the family Flaviviridae that are dependent on LDLR.